Healthcare Supply Chain Framework for Optimization Process: Literature Review and Some Issues - Jeanne Switasarry Alexandrea, Parama Kartika Dewa (International Journal of Advanced Science and Technology, 2020)
At present, conditions throughout the world require good health services, coronavirusattacks make this relevant for further research. Good health services need support fromgood supply chain management. Performance in the supply chain can be operated well ifa framework for the supply chain structure is available. The heathcare supply chainmanagement system will be different when the context and environment are different fromnormal conditions. In the case of the Covid-19 pandemic the community needs a fastresponse from hospital services. The speed of the number of patients increasesexponentially. This will affect the performance of the manufacturing supply chain wherehuman resources will be reduced exponentially. The limited number of hospitals that arereferred to patient care is limited, increasing the complexity of the problems faced by thehealthcare supply chain. The challenge that must be resolved is how the availableresources are optimized to achieve their main objectives. For the stages of answering thischallenge, an appropriate framework is needed. Based on the literature review andinterviews with parties involved in the healthcare supply chain, a framework wasdeveloped to manage the healthcare supply chain. The main components of the proposedframework include: the objective function, performance indicators, constraints, risk, andplayers.